Pengaruh Harga, Kualitas Produk dan Kualitas Pelayanan terhadap Keputusan Pembelian pada PT. Sentrik Persada Nusantara di Denpasar - Gunawan, I Made Adi; Wijaya, Putu Yudy; Mashyuni, Ida Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This research was conducted to determine the effect of price, product quality and service quality on purchasing decisions at PT. Sentrik Persada Nusantara. The population in this study are all consumers of PT. Sentrik Persada Nusantara from January to July 2022. The sample used in this study was 100 respondents who were determined using the accidental sampling method. Data analysis techniques used in this study were validity, reliability, classical assumptions, multiple linear regression, coefficient of determination, t test and F test. Based on the results of the study it can be seen that: (1) Price has a positive and significant effect on purchasing decisions. (2) Product quality has a positive and significant effect on purchasing decisions. (3) Service Quality has a positive and significant effect on purchasing decisions. (4) Price, product quality, and service quality have a positive and significant effect on purchasing decisions. The magnitude of the influence of the independent variables on purchasing decisions is 61.7%. Looking at the research results, PT. Sentrik Persada Nusantara in the future must readjust the prices of the products being sold, try to keep the prices not more expensive than other competitors so that later consumers will be interested in buying products from PT. Sentrik Persada Nusantara.